2018
DOI: 10.3906/sag-1704-1
|View full text |Cite
|
Sign up to set email alerts
|

Translocation breakpoints of chromosome 3 in male carriers: a report oftwelve cases and a review of the literature

Abstract: Background/aim: This study aimed to explore the breakpoints in chromosome 3 translocation and the clinical features present in male carriers to enable informed genetic counseling of these patients. Materials and methods: A total of 5235 men who were infertile or receiving counseling for infertility were recruited. Cytogenetic analyses were performed using G-banding. A search for translocations on chromosome 3 involved in male infertility was performed using PubMed, Google Scholar, and CNKI. The relationships o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Recently, we reported and reviewed the relationship between translocation breakpoints of chromosomes 2, 3, 5, and 6, and infertility for male carriers [9, 10, 11, 12, 13]. Previous studies indicated that chromosome 9 translocations are involved in reduced male fertility and increased chance of miscarriage in the female partner [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported and reviewed the relationship between translocation breakpoints of chromosomes 2, 3, 5, and 6, and infertility for male carriers [9, 10, 11, 12, 13]. Previous studies indicated that chromosome 9 translocations are involved in reduced male fertility and increased chance of miscarriage in the female partner [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The chromosomes and specific breakpoints involved in the translocation are closely related to reproductive abnormalities [16,17]. Chromosomal translocation can increase the frequency of spermatozoa carrying an abnormal chromosome constitution, and some translocation breakpoints can disrupt important genes involved in spermatogenesis [10]. Testis-specific protein kinase 1 gene ( TESK1 ) is located on chromosome 9p13.3 and is specifically expressed in testicular germ cells [18].…”
Section: Introductionmentioning
confidence: 99%